2019
DOI: 10.3389/fmed.2019.00100
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sv129 Mice as a Susceptible Model to Leishmania amazonensis

Abstract: Leishmaniasis is a complex of neglected diseases caused by parasites of the genus Leishmania , such as Leishmania (Leishmania) amazonensis , the ethiologic agent of diffuse cutaneous leishmaniasis in Brazil. In this work, we investigated a new experimental model of infection for L. amazonensis : the Sv129 mouse. First, we subcutaneously infected Sv129 mice with 2 × 10 5 or 2 × 10 6 L. amazonensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…We previously showed that L.amazonensis infection induces an increase of IL-17A-producing γδ T cells in Sv129 mice 31 . However, their precise contribution to the IL-17A response in L. amazonensis infection was not known before the present study.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…We previously showed that L.amazonensis infection induces an increase of IL-17A-producing γδ T cells in Sv129 mice 31 . However, their precise contribution to the IL-17A response in L. amazonensis infection was not known before the present study.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously demonstrated that L. amazonensis infection of Sv129 mice fails to induce expansion of IFN-γ producing CD4 and CD8 T cells, but it triggers the expansion of IL-17A producing γδ T cells 31 . To determine the main source of IL-17A in L. amazonensis infection, we performed a flow cytometry analysis of the draining popliteal lymph node of mice infected in the footpad.…”
Section: γδ T Cells Are the Main Source Of Il-17a In Leishmania Amazo...mentioning
confidence: 98%
See 2 more Smart Citations
“…However, it is worth mentioning that, at the peak phase of infection until the end of the experiment, the number of parasites was similar. Recently, dos-Santos et al [33] reported that, during infection with the L. amazonensis Josefa strain in Sv129 mice, although there was a difference in the time of lesion development between inoculums of 2 × 10 5 and 2 × 10 6 , the lesions were equal at the end of 16 weeks of infection and there was not a difference in the parasite load at the end. Thus, the inoculation dose can greatly influence the profile of Leishmania infection.…”
Section: Discussionmentioning
confidence: 99%